Sulfonation of phenols extracted from the pyrolysis oil of oil palm shells for enhanced oil recovery. - Awang, Mariyamni (2008)

(untitled)
The cost of chemicals prohibits many technically feasible enhanced oil recovery methods to be applied in oil fields. It is shown that by-products from oil palm processing can be a source of valuable chemicals. Analysis of the pyrolysis oil from oil palm shells, a by-product of the palm oil industry, reveals a complex mixture of mainly phenolic compounds, carboxylic acids, and aldehydes. The phenolic compounds were extracted from the pyrolysis oil by liquid-liquid extraction using alkali and an organic solvent and analyzed, indicating the presence of over 93% phenols and phenolic compounds. Simultaneous sulfonation and alkylation of the pyrolysis oil was carried out to produce surfactants for application in oil fields. The lowest measured surface tension and critical micelle concentration was 30.2 mNm(-1) and 0.22 wt%, respectively. Displacement tests showed that 7-14% of the original oil in place was recovered by using a combination of surfactants and xanthan (polymer) as additives.